Political ideology and vaccination willingness: implications for policy design - Debus, Marc; Tosun, Jale (Policy sciences, 2021)
The COVID-19 pandemic has forced governments to impose major restrictions on individual freedom in order to stop the spread of the virus. With the successful development of a vaccine, these restrictions are likely to become obsolete—on the condition that people get vaccinated. However, parts of the population have reservations against vaccination. While this is not a recent phenomenon, it might prove a critical one in the context of current attempts to manage the COVID-19 pandemic. Consequently, the task of designing policies suitable for attaining high levels of vaccination deserves enhanced attention. In this study, we use data from the Eurobarometer survey fielded in March 2019. They show that 39% of Europeans consider vaccines to cause the diseases which they should protect against, that 50% believe vaccines have serious side effects, that 32% think that vaccines weaken the immune system, and that 10% do not believe vaccines are tested rigorously before authorization. We find that—even when controlling for important individual-level factors—ideological extremism on both ends of the spectrum explains skepticism of vaccination. We conclude that policymakers must either politicize the issue or form broad alliances among parties and societal groups in order to increase trust in and public support for the vaccines in general and for vaccines against COVID-19 in particular, since the latter were developed in a very short time period and resulted—in particular in case of the AstraZeneca vaccine—in reservations because of the effectiveness and side effects of the new vaccines.
Gesehen am 18.07.2023